Differential effects of raloxifene and continuous combined hormone replacement therapy on biochemical markers of cardiovascular risk: Results from the Euralox I study - (:unkn) unknown (Informa Healthcare, 2001)
Objective: To compare the effects of the selective estrogen receptor modulator (SERM) raloxifene (Evista®) and a continuous combined hormone replacement therapy (ccHRT) formulation containing estradiol and norethisterone acetate (Kliogest®) on lipid and fibrinogen levels of postmenopausal women. Methods: Euralox 1 was a prospective, randomized, double-blind trial. After a placebo wash-out, healthy postmenopausal women (n = 1008, average age 56.1 ± 4.9 years) with a health risk profile that suggested a potential benefit from either treatment were randomly assigned to either 60 mg raloxifene or ccHRT consisting of 2 mg estradiol and 1 mg norethisterone acetate (NETA) per day for 6 months. Measurements: Total cholesterol, low-density lipoprotein (LDL) cholesterol, highdensity lipoprotein (HDL) cholesterol with its fractions HDL2 and HDL3, the LDL/HDL ratio, triglycerides and fibrinogen were asessed at baseline and after 6 months or on early drop-out. Results: Baseline values were comparable between the two groups. Blood samples of 841 women (83.4%) were available at baseline and endpoint. Total and LDL cholesterol decreased statistically significantly from baseline to endpoint in both treatment arms (by 7.2% and 3.8% with raloxifene and by 13.0% and 8.9% with ccHRT, respectively). Raloxifene produced a statistically significant increase in HDL cholesterol by 4.2%, while ccHRT induced a decline by 9.5%. Triglycerides were moderately suppressed with raloxifene and ccHRT, by 3.6 and 5.4%, respectively. Fibrinogen fell by 7.0% with raloxifene and rose by 3.6% with ccHRT. Conclusions: Continuous combined HRT was associated with decreases in total cholesterol and LDL cholesterol about twice as large as with raloxifene, but also with a decrease in HDL cholesterol. The smaller decreases in total cholesterol and LDL cholesterol associated with raloxifene were accompanied by an increase in HDL cholesterol and a decrease in fibrinogen. In conclusion, raloxifene affects fibrinogen concentrations and the overall cholesterol profile more favorably than ccHRT; these differences may have important implications for the reduction of cardiovascular disease.
Keywords: Cholesterol; Estradiol; Fibrinogen; Hormone replacement therapy; Norethisterone; Raloxifene; Triglycerides